O temor da mudança na clínica do vazio - Aoki, Neide Aparecida de Oliveira Santos (2013)
Civilization has experienced a new discomfort. Despite the great technological advances, there still exist feelings of mental inertia, of loneliness and of a non-sense life. Individuals are anonymous, suffer from abandonment with no chance for singularity. The psychoanalytic clinic today expresses this pounding symptom being the main complaints this vague sensation of emptiness, meaninfullness, difficulty in having an identity and love for oneself. Psychoanalysis has emphasized the increasing necessity to highlight what has conventionally been called the pathology of emptiness that is, the clinical approach that is close to psychosis, the relationship with others and the fragile egoic structure that represent neuvragic issues. Analysts are challenged to accept a relationship with nothing , to experience the abysm of no me without being absorbed by it. The opportunity of being with these patients has been a necessary topic for the psychoanalyst reflection. Literature presents the awakening of these questions alerting for its urgency. Therefore, this paper aims at exploring the emptiness experiences exposed by these patients with the theoretical about the theme in order to understand the peculiarities of such psychic behavior, to think of ways of reaching it, to look for literary and cinematographic works that give voice and form to this mental state once words are almost inexistent. So, there can be a deep ludic proximity of such primitive living experience of not being . Theory and art interact to try to reach the indescribable of the analytic involvement with such patients guided by the reasons that could be enhancing this lethargic mental state and the barriers that could prevent the changes. Would it be possible to exist some specification of the analytical work in such cases? Consequently the theoretical conceptual psychoanalytic referential was adopted. The core are the bionianas theories plus the contribution from Tustin and A. Ferro that broaden the Bion´s view concerning thought structures and autisticos functioning and emotions blunt. The illustrative artistic works such as A menina de lá by Guimarães Rosa, Bartley by Melville, A hora da estrela by Lispector, A sonata de outono by Bergamn and The Martin Child by Bass and Tolins display the live theory. This is an attempt to translate in a symbolic and representative way nuances of investigated themes. Patients and analysts dressed as characters were bestowed with the artist delicateness and with knowledge strength supported by theory. During the investigative way it is possible to conclude that feelings of emptiness and no meaning have their roots in early environmental failures. The mother presence attending the child´s necessities interfere with tolerance incapacity toward frustration when there is no available forms to deal with it. This fact leads to an affection and vital impulse blockage that develops inhibitions, emptiness sensation and boredom. These patients were prevented from having the minimal conditions to connect with themselves without threats. This way they refrain emotions as they are felt as a catastrophic threat. The relationship with these patients, therefore demands patience and vitality to approach a mind in which threat to bond is the main characteristic. This could help this abysm unspeakably bad